2017
DOI: 10.1109/tcomm.2017.2737018
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Transmission of Spatially Coupled LDPC Code Chains

Abstract: We propose a novel encoding/transmission scheme called continuous chain (CC) transmission that is able to improve the finite-length performance of a system using spatially-coupled low-density parity-check (SC-LDPC) codes. In CC transmission, instead of transmitting a sequence of independent codewords from a terminated SC-LDPC code chain, we connect multiple chains in a layered format, where encoding, transmission, and decoding are performed in a continuous fashion. The connections between chains are created at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This effect is more severe for smaller values M. However, since SC-LDPC code ensemble has a linear growth of minimum distance with block length nM, the codes with small cycles or low-weight stopping sets can hardly be found for sufficiently large M. Therefore, when M increases to a few thousands, the effects on the prediction accuracy will be small enough to be ignored. Next, we extended the analysis to the case of connecting three different chains and considered the ensemble P (3,6,3,9,3,12,15). The mean value r1 (τ) with M = 200 and different is plotted in Figure 6.…”
Section: Performance Analysis and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect is more severe for smaller values M. However, since SC-LDPC code ensemble has a linear growth of minimum distance with block length nM, the codes with small cycles or low-weight stopping sets can hardly be found for sufficiently large M. Therefore, when M increases to a few thousands, the effects on the prediction accuracy will be small enough to be ignored. Next, we extended the analysis to the case of connecting three different chains and considered the ensemble P (3,6,3,9,3,12,15). The mean value r1 (τ) with M = 200 and different is plotted in Figure 6.…”
Section: Performance Analysis and Resultsmentioning
confidence: 99%
“…Similar results can be observed that, when approaching the threshold * = 0.3114, the r1 (τ * ) values gradually decrease to approximately zero. In Table 2, the δ 1 (τ * ) values are calculated for the codes generated from the ensemble P (3,6,3,9,3,12,15). The predicted error probabilities and the simulated ones for these codes are shown in Figure 7.…”
Section: Performance Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations